Early CRP Trends in Childhood Osteomyelitis Predict Complicated Disease. Issue 1 (17th January 2023) - Hunter, Sarah; Baker, Joseph F.
Abstract : Background: Acute hematogenous osteomyelitis (AHO) remains a cause of severe illness among children. Contemporary research aims to identify predictors of acute and chronic complications. Trends in C-reactive protein (CRP) after treatment initiation may predict disease course. We have sought to identify factors associated with acute and chronic complications in the New Zealand population. Methods: A retrospective review of all patients younger than16 years with presumed AHO presenting to a tertiary referral centre between 2008 and 2018 was performed. Multivariate was analysis used to identify factors associated with an acute or chronic complication. An "acute" complication was defined as the need for 2 or more surgical procedures, a hospital stays longer than 14 days, or recurrence despite intravenous antibiotics. A "chronic" complication was defined as growth or limb length discrepancy, avascular necrosis, chronic osteomyelitis, pathologic fracture, frozen joint, or dislocation. Results: One hundred fifty-one cases met the inclusion criteria. The median age was 8 years (69.5% male). Within this cohort, 53 (34%) experienced an acute complication and 18 (12%) a chronic complication. Regression analysis showed that contiguous disease, delayed presentation, and failure to reduce CRP by 50% at day 4/5 predicted an acutely complicated disease course. Chronic complication was predicted by the need for surgical management and failed CRP reduction by 50% at day 4/5. Conclusions: CRP trends over 96 hours after the commencement of treatment differentiate patients with AHO likely to experience severe disease. Level of Evidence: Level II, retrospective study